Use of Imaging Techniques to Illuminate Dynamics of Hematopoietic Stem Cells and Their Niches - Morikawa, Takayuki; Takubo, Keiyo (Frontiers in Cell and Developmental Biology, 2017)
Continuous generation of blood cells over an organism's lifetime is supported by hematopoietic stem/progenitor cells (HSPCs) capable of producing all hematopoietic cell subtypes. Adult mammalian HSPCs are localized to bone marrow and regulated by their neighboring microenvironment, or “niche.” Because interactions of HSPCs with their niches are highly dynamic and complex, the recent development of imaging technologies provides a powerful new tool to understand stem cell/niche biology. In this review, we discuss recent advances in our understanding of dynamic HSPC/niche interactions during development, homeostasis, disease states or aging with a focus on studies advanced by imaging analysis. We also summarize methods to visualize HSPCs and niche cells in vivo, including use of HSPC reporter mice and chemical probes. Findings emerging from these investigations could suggest novel therapies for diseases and aging.